2023
DOI: 10.1371/journal.pone.0283318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of integrated hospital treatment on the default mode, salience, and frontal-parietal networks in anorexia nervosa: A longitudinal resting-state functional magnetic resonance imaging study

Abstract: The psychopathology of patients with anorexia nervosa has been hypothesized to involve inappropriate self-referential processing, disturbed interoceptive awareness, and excessive cognitive control, including distorted self-concern, disregard of their own starvation state, and extreme weight-control behavior. We hypothesized that the resting-state brain networks, including the default mode, salience and frontal-parietal networks, might be altered in such patients, and that treatment might normalize neural funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The neurobiology of AN is poorly understood (Frank, Shott & DeGuzman, 2019), however the use neuroimaging, particularly resting state functional magnetic resonance imaging (rsfMRI) offers promise in demonstrating neurophenotypes that characterise AN. Previous work, utilising rsfMRI, has characterised atypical connectivity in individuals with AN involving temporal regions (Olivo et al, 2018), as well as the ventral attention, default mode and the salience networks (Spalatro et al, 2019; Gondo et al, 2023). Atypical connectivity, as demonstrated by rsfMRI, is also not just isolated to the underweight stage of illness course (Boehm et al, 2016; Gondo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The neurobiology of AN is poorly understood (Frank, Shott & DeGuzman, 2019), however the use neuroimaging, particularly resting state functional magnetic resonance imaging (rsfMRI) offers promise in demonstrating neurophenotypes that characterise AN. Previous work, utilising rsfMRI, has characterised atypical connectivity in individuals with AN involving temporal regions (Olivo et al, 2018), as well as the ventral attention, default mode and the salience networks (Spalatro et al, 2019; Gondo et al, 2023). Atypical connectivity, as demonstrated by rsfMRI, is also not just isolated to the underweight stage of illness course (Boehm et al, 2016; Gondo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work, utilising rsfMRI, has characterised atypical connectivity in individuals with AN involving temporal regions (Olivo et al, 2018), as well as the ventral attention, default mode and the salience networks (Spalatro et al, 2019; Gondo et al, 2023). Atypical connectivity, as demonstrated by rsfMRI, is also not just isolated to the underweight stage of illness course (Boehm et al, 2016; Gondo et al, 2023). Cross-sectional studies with weight restored individuals with AN has suggested altered connectivity involving the frontoparietal network (Boehm et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation